Pelestarian dan Adaptasi Ritual Mappadendang oleh Etnis Bugis di Wilayah Penduduk Asli Kaili - Khairul, Moh.; Junaidi, M.; Ariyani, Risma; Hapsa, Hapsa (CV. Social Politic Genius (SIGn), 2023)
This research aims to understand the role of the Mappadendang ritual as part of the Bugis ethnicity’s identity in the area of the Kaili indigenous people and the benefits of the Mappadendang ritual for social life in Kasimbar Palapi Village. This research uses an ethnographic analysis. Ethnographic analysis is an approach that begins with field facts, analyzes them based on cultural theories and relevant arguments to explore the cultural situation of the community, and ultimately yields a conclusion. The results show that the Mappadendang ritual is an essential means for the Bugis ethnicity in the area of the Kaili indigenous people to maintain and express their cultural identity. Through elements such as traditional cake, traditional cuisine, and bodo attire, the Bugis ethnicity demonstrates solidarity and pride in their cultural heritage. Moreover, this tradition provides broad social benefits, including strengthening interethnic fellowship, enhancing social relationships, fostering social care, reinforcing cultural identity, and boosting the spirit of rice farming. Therefore, it is recommended that the Department of Education and Culture of Parigi Moutong Regency support the preservation and adaptation of the Mappadendang ritual by providing facilities and platforms for the Bugis ethnicity and other ethnicities to showcase and share their cultural values. The government should also ensure the availability and affordability of fertilizers and streamline the irrigation process for rice farming, which is a crucial element of the Mappadendang ritual. To the traditional leaders of the Bugis ethnicity, Kaili indigenous people, and other ethnic groups, it is recommended that they continue collaborating in organizing the Mappadendang ritual as a platform for interethnic fellowship and to strengthen cultural identity. The community in Kasimbar Palapi Village is encouraged to continue participating in and supporting this activity. With good cooperation among all parties, the Mappadendang ritual can continue to be preserved as a valuable cultural heritage, enriching diversity and strengthening cultural identity in a region rich with multiple identities.